(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
This article is dedicated to the "Youth Forum" and the appeals of President Shavkat Mirziyoyev Miromonovich in the Oliy Majlis, about the opportunities created for young people, who are the backbone and pride of our state.